A serological study of leptospiral infection in buffaloes in Malaysia. - Bahaman, A. R.; Ibrahim, A. L.; Othman, A. M. (1986)
A serological survey of 13 herds of buffaloes from 2 large established farms and 3 groups of smallholdings in Malaysia showed 132 (31.9%) of the animals examined had leptospiral titres (>1:40) to one or more leptospiral serovars by the microscopic agglutination test (MAT). Seventy eight (18.8%) of the buffaloes had titres to serovar hardjo, 41 (9.9%) to serovar tarassovi,and 44 to serovars icterohemorrhagiae,pomona and pyrogenes. Results showed all but one of the herds had experienced hardjo infection,with individual herd prevalence ranging from 5.6% to 32.1%. It is seen that sporadic hardjo infection is not uncommon in buffaloes. More detailed studies are necessary to elucidate the epidemiology of leptospiral infection in buffaloes.